2019
DOI: 10.1093/mnras/stz2907
|View full text |Cite
|
Sign up to set email alerts
|

Early-type galaxy density profiles from IllustrisTNG – II. Evolutionary trend of the total density profile

Abstract: We study the evolutionary trend of the total density profile of early-type galaxies (ETGs) in IllustrisTNG. To this end, we trace ETGs from z = 0 to z = 4 and measure the power-law slope γ of the total density profile for their main progenitors. We find that their γ steepen on average during z ∼ 4 − 2, then becoming shallower until z = 1, after which they remain almost constant, aside from a residual trend of becoming shallower towards z = 0. We also compare to a statistical sample of ETGs at different redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 153 publications
(250 reference statements)
11
34
0
Order By: Relevance
“…So we assume the effects are currently not significant in our case. A similar result is also reported recently by Wang et al (2019) where they find the density slope to remain nearly invariant after z=1 with a mild increase towards z = 0. However, in our case, a full-scale redshift evolution study is beyond the scope of this work.…”
Section: Potential Systematicssupporting
confidence: 91%
“…So we assume the effects are currently not significant in our case. A similar result is also reported recently by Wang et al (2019) where they find the density slope to remain nearly invariant after z=1 with a mild increase towards z = 0. However, in our case, a full-scale redshift evolution study is beyond the scope of this work.…”
Section: Potential Systematicssupporting
confidence: 91%
“…The evolution with redshift implied by gravitational lensing results is at odds with the predictions of simulations, which indicate steeper slopes with higher redshifts (Remus et al 2013(Remus et al , 2017Wang et al 2019), and is also inconsistent to the observed mass-size growth of early-type galaxies with redshift as inferred from stellar light (Franx et al 2008;van Dokkum et al 2010;van der Wel et al 2014;Mowla et al 2019). Furthermore, gravitational lensing is necessarily biased towards the most massive, dense objects that act as effective lenses, and this can impact knowledge of the distribution of total mass density slopes (Mandelbaum, van de Ven & Keeton 2009).…”
mentioning
confidence: 71%
“…However, strong evidence for evolution in the small redshift range of the Frontier Fields sample is not expected, considering also the intrinsic scatter of the sample and associated density slope uncertainties. The IllustrisTNG simulations indicate little evolution in density slope below z ∼ 1, due to evolution via gas-poor mergers (Wang et al 2019). The Magneticum simulations predict a mild trend with redshift given by the relation γ = −0.21z − 2.03 (Remus et al 2017).…”
Section: Correlations With Total Mass Density Slopementioning
confidence: 90%
See 2 more Smart Citations